Gut Microbiome Signatures Are Predictive of Infectious Risk Following Induction Therapy for Acute Myeloid Leukemia. (22nd August 2019) - Galloway-Peña, Jessica R; Shi, Yushu; Peterson, Christine B; Sahasrabhojane, Pranoti; Gopalakrishnan, Vancheswaran; Brumlow, Chelcy E; Daver, Naval G; Alfayez, Mansour; Boddu, Prajwal C; Khan, Md Abdul Wadud; Wargo, Jennifer A; Do, Kim-Anh; et al.
Abstract: Background: The majority of studies that provide insights into the influence of the microbiome on the health of hematologic malignancy patients have concentrated on the transplant setting. Here, we sought to assess the predictive capacity of the gastrointestinal microbiome and its relationship to infectious outcomes in patients with acute myeloid leukemia (AML). Methods: 16s rRNA-based analysis was performed on oral swabs and stool samples obtained biweekly from baseline until neutrophil recovery following induction chemotherapy (IC) in 97 AML patients. Microbiome characteristics were correlated with clinical outcomes both during and after IC completion. Results: At the start of IC, higher stool Shannon diversity (hazard ratio [HR], 0.36; 95% confidence interval [CI], .18–.74) and higher relative abundance of Porphyromonadaceae (HR, 0.36; 95% CI, .18–.73) were associated with increased probability of remaining infection-free during neutropenia. A baseline stool Shannon diversity cutoff of <2 had optimal operating characteristics for predicting infectious complications during neutropenia. Although 56 patients received therapy >72 hours with a carbapenem, none of the patients had an infection with an extended spectrum β-lactamase–producing organism. Patients who received carbapenems for >72 hours had significantly lower α-diversity at neutrophil recovery ( P = .001) and were approximately 4 times more likely to have infection in the 90 days following neutrophil recovery (HR, 4.55; 95% CI, 1.73–11.93). Conclusions: Our results suggest that gut microbiome evaluation could assist with infectious risk stratification and that improved targeting of antibiotic administration during IC could decrease subsequent infectious complications in AML patients. Baseline microbiome diversity is a strong independent predictor of infection during acute myeloid leukemia induction chemotherapy (IC) among clinical and microbiome covariates. Higher baseline levels of Porphyromonadaceae appear protective against infection, while carbapenem use is associated with consequences to the microbiome and infection susceptibility post-IC.